Actionable knowledge for ecological intensification of agriculture. Issue 4 (May 2016) - Geertsema, Willemien; Rossing, Walter AH; Landis, Douglas A; Bianchi, Felix JJA; van Rijn, Paul CJ; Schaminée, Joop HJ; Tscharntke, Teja; van der Werf, Wopke
Abstract : Ecological intensification of agriculture (EI) aims to conserve and promote biodiversity and the sustainable use of associated ecosystem services to support resource‐efficient production. In many cases EI requires fundamental changes in farm and landscape management as well as the organizations and institutions that support agriculture. Ecologists can facilitate EI by engaging with stakeholders and, in the process, by generating "actionable knowledge" (that is, knowledge that specifically supports stakeholder decision making and consequent actions). Using three case studies as examples, we propose four principles whereby science can improve the delivery of actionable knowledge for EI: (1) biodiversity conservation helps to ensure the delivery of ecosystem services, (2) management of ecosystem services benefits from a landscape‐scale approach, (3) ecosystem service trade‐offs and synergies need to be articulated, and (4) EI is associated with complex social dynamics involving farmers, governments, researchers, and related institutions. These principles have the potential to enhance adoption of EI, but institutional and policy challenges remain.